Association Studies Suggest a Key Role for Endothelin-1 in the Pathogenesis of Preeclampsia and the Accompanying Renin–Angiotensin–Aldosterone System Suppression. Issue 6 (June 2015) - Verdonk, Koen; Saleh, Langeza; Lankhorst, Stephanie; Smilde, J.E. Ilse; van Ingen, Manon M.; Garrelds, Ingrid M.; Friesema, Edith C.H.; Russcher, Henk; van den Meiracker, Anton H.; Visser, Willy; Danser, A.H. Jan
Abstract : Women with preeclampsia display low renin–angiotensin–aldosterone system activity and a high antiangiogenic state, the latter characterized by high levels of soluble Fms-like tyrosine kinase (sFlt)-1 and reduced placental growth factor levels. To investigate whether renin–angiotensin–aldosterone system suppression in preeclampsia is because of this disturbed angiogenic balance, we measured mean arterial pressure, creatinine, endothelin-1 (ET-1), and renin–angiotensin–aldosterone system components in pregnant women with a high (≥85; n=38) or low (<85; n=65) soluble Fms-like tyrosine kinase-1/placental growth factor ratio. Plasma ET-1 levels were increased in women with a high ratio, whereas their plasma renin activity and plasma concentrations of renin, angiotensinogen, and aldosterone were decreased. Plasma renin activity–aldosterone relationships were identical in both the groups. Multiple regression analysis revealed that plasma renin concentration correlated independently with mean arterial pressure and plasma ET-1. Plasma ET-1 correlated positively with soluble Fms-like tyrosine kinase-1 and negatively with plasma renin concentration, and urinary protein correlated with plasma ET-1 and mean arterial pressure. Despite the lower plasma levels of renin and angiotensinogen in the high-ratio group, their urinary levels of these components were elevated. Correction for albumin revealed that this was because of increased glomerular filtration. Subcutaneous arteries obtained from patients with preeclampsia displayed an enhanced, AT2 receptor-mediated response to angiotensin II. In conclusion, a high antiangiogenic state associates with ET-1 activation, which together with the increased mean arterial pressure may underlie the parallel reductions in renin and aldosterone in preeclampsia. Because ET-1 also was a major determinant of urinary protein, our data reveal a key role for ET-1 in the pathogenesis of preeclampsia. Finally, the enhanced angiotensin responsiveness in preeclampsia involves constrictor AT2 receptors. Abstract : Supplemental Digital Content is available in the text.